2006
DOI: 10.1309/0pl3c674m39d6gen
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Automated Malaria Discriminant Factor Using VCS Technology

Abstract: Malaria diagnosis presents a challenge to all laboratories. There is a need for rapid, sensitive, and cost-effective screening on all samples, particularly in areas where malaria is endemic. Response to malaria infection involves an increased monocyte count and production of large activated monocytes. These changes can be detected by volume, conductivity, and scatter (VCS) technology on certain automated blood cell counters (Beckman Coulter, Miami, FL). The SD of the volume of lymphocytes and monocytes demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
(29 reference statements)
3
35
0
1
Order By: Relevance
“…21 Three prototypes of analyzers have been evaluated for malaria diagnosis. The Cell-Dyn analyzers detect monocyte-coded depolarizing events corresponding to hemozoin-laden macrophages 8 with a maximum sensitivity and specificity of 97% 22 and 98%, 23 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Three prototypes of analyzers have been evaluated for malaria diagnosis. The Cell-Dyn analyzers detect monocyte-coded depolarizing events corresponding to hemozoin-laden macrophages 8 with a maximum sensitivity and specificity of 97% 22 and 98%, 23 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the Coulter analyzers, a malaria discriminant factor that uses monocyte and lymphocyte DC measurements has a maximum sensitivity and specificity of 98% and 96.9%, respectively. 4,21 More recently, using the XE-2100 analyzer, two case series in South Korea, one with 16 and one with 3 P. vivax -infected patients, described pseudoeosinophilia and abnormal granulocyte-coded events in the DIFF scatterplot in approximately 38% of samples. 9,10 In 2008, Huh and others 5 in South Korea compared these two findings against thick-film malaria diagnosis in 144 samples of P. vivax -infected patients and in 319 samples from febrile patients, reporting a sensitivity of 69.4% and a specificity of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The second method also used a Cell-Dyn � 3500, and analyzed depolarized laser light (DLL) to detect malaria infection, with an overall sensitivity of 72% and specificity of 96% [82]. The third technique used a Beckman Coulter ACC to detect increases in activated monocytes by volume, conductivity, and scatter (VCS), with 98% sensitivity and 94% specificity [83]. Although promising, none of the 3 techniques is routinely available in the clinical laboratory; further studies are required to improve and validate the instrument and its software.…”
Section: Automated Blood Cell Counters (Acc)mentioning
confidence: 99%
“…13 Some work on the changes in VCS parameters has been undertaken in patients with acute malaria. In a study conducted by Briggs et al, 14 response to malarial infection was shown to cause an increased monocyte count and production of large activated monocytes detectable by the VCS technology. We also observed a significant increase in the mean MV as well as in their relative quantity in malarial infection.…”
mentioning
confidence: 99%
“…This could be attributed to racial and, possibly, environmental differences in the two populations studied. Also, the values put forth in the study by Briggs et al 14 are of a single patient of falciparum malaria. It is not a scientific comparison, nonetheless, it gives an insight into the alteration of VCS parameters in malaria, given the paucity of literature on the subject.…”
mentioning
confidence: 99%